2016
DOI: 10.5935/0103-5053.20160113
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atmosphere on Elemental Mercury Release During Thermal Treatment of Two Bituminous Coals

Abstract: The dynamic release behavior of elemental Hg (Hg 0 ) during thermal treatment of two bituminous coals was studied under N 2 , CO 2 and air atmospheres. The results show that the profiles of Hg 0 released present several peaks during thermal treatment of two bituminous coals. The Hg peak profiles for the same coal are different with the different atmosphere used. The amount of Hg 0 released from the coals is about 92-94, 73-74 and 31-33% under N 2 , CO 2 and air atmosphere, respectively. This indicates that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It is reported that most of the Hg released from coal or coal gangue is in the form of Hg 0 under N 2 , which is very consistent with the result of this study. , Meanwhile, it can be observed that the Hg 2+ RR in air is higher than that in a N 2 atmosphere, especially for the 1# coal gangues. Actually, the air is different from the N 2 atmosphere, because of the existence of oxygen.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…It is reported that most of the Hg released from coal or coal gangue is in the form of Hg 0 under N 2 , which is very consistent with the result of this study. , Meanwhile, it can be observed that the Hg 2+ RR in air is higher than that in a N 2 atmosphere, especially for the 1# coal gangues. Actually, the air is different from the N 2 atmosphere, because of the existence of oxygen.…”
Section: Resultssupporting
confidence: 90%
“…It can be explained that some organic matters in coal gangue are burned under the presence of oxygen, leading to a higher VY under air. However, the HgRR under air atmosphere is lower than that under N 2 . As stated above, it is possibly due to the oxidation of Hg 0 by oxygen in air. , …”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations